UPAYA PERSERIKATAN BANGSA-BANGSA (PBB) SEBAGAI ORGANISASI INTERNASIONAL DALAM MENENGAHI KONFLIK RUSIA DAN UKRAINA PADA TAHUN 2022 - Sayyidul Mubin; Risky Moehamad Adha (Jurnal Pena Wimaya, 2022)
The Russia-Ukraine tensions that have occurred this year have caught the world's attention. This tension initially occurred with the deployment of hundreds of thousands of Russian troops on the Ukrainian border and the involvement of NATO, including the United States, which began to take steps, so that the escalation of the conflict was inevitable. This paper uses an institutional liberalism approach and the data are taken using the author's literature review from various related literatures that are relevant to the writing .The actions of NATO which participated in responding to it became a threat to Russia which eventually worsened the conflict on the Ukrainian border. As the largest international organization, the United Nations has a big role in this conflict as a mediating party that can find a way out from both sides. This paper analyzes the role of the United Nations in seeking conclusions on these problems, regarding how its roles, objectives, and functions are to find a conflict resolution. As the international community, every country needs to take part in overcoming the ongoing conflict, and it is a great obligation for the United Nations to be the main tool in resolving this conflict, given the large capabilities it has, and the many countries that can contribute, so that later the Russia-Ukrainian conflict can be resolved quickly.Keywords: Russia-Ukraine, NATO, UN, conflict resolution